Progressive retrieval practice leads to greater memory for image-word pairs than standard retrieval practice. Issue 7 (9th August 2022) - Liu, Shaohang; Zheng, Zihao; Kent, Christopher; Briscoe, Josie
ABSTRACT: The benefits of retrieval practice on learning are robust and have transferred from laboratory findings to many real-world educational settings. We report two experiments that investigated a novel retrieval practice technique for remembering arbitrary associations (image-word pairs), with and without reward as a motivator. As well as typical retrieval practice and restudy conditions, we added a third condition of graded retrieval practice in which the image cue was partially released in a progressive process. Experiment 1 found significant benefits of retrieval practice over restudy, with an additional benefit of graded retrieval practice compared with standard retrieval practice after a 48-hour delay between study and retrieval. Experiment 2 included a reward manipulation by giving participants money based on their memory performance. The findings replicated the retrieval practice effects observed in Experiment 1, including a robust advantage for graded retrieval practice. Reward neither changed the additive advantage of graded recall nor the benefit of retrieval practice. The present study adds to the literature indicating that retrieval with progressive retrieval cues can boost the benefit of retrieval practice by generating repeated retrieval attempts. This benefit occurs most for items that are neither too easy nor too challenging to retrieve.